FEASIBILITY TEST OF HEREDITY CIRCLE (CROSS) PRACTICUM GUIDE ON INHERITANCE MATERIALS FOR INQUIRY-BASED STUDENTS IN CLASS XII - Nada Qitriyyah Suhaika; Erfina Damayanti Firdaus; Bakara Ramadhan; Ade Suryanda (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
This study aims to develop and analyze content feasibility, presentation feasibility, language feasibility in practicum guides in the application of heredity circles using the 4-D model. The method used is development (Development Research). The research was designed with ADDIE's design development model (Analysis, Design, Development, Implementation and Evaluation). The data used are qualitative and quantitative data. Quantitative data was obtained from questionnaires and tests while qualitative data came from criticism and suggestions for the guide product by validating the material and student responses. The evaluation aspect at the 1st validation stage obtained an average result of 53.38% and increased in the 2nd stage validation by 8.78% to 62.16% where the criteria that were in the good enough category changed to be good. Based on the research results obtained, it can be concluded that the feasibility test of the Lingkaran Hereditas (LINTAS) practicum guide on inheritance material for inquiry-based class XII students can be declared feasible, valid, and effective for use in schools both in terms of content, presentation, to language used.